Garis Panduan Mengenai Amalan Sihir Menurut Perspektif Islam - Muna bin Hamzan (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2022)
This study aims to provide general guidance to religious authorities and the prosecution on the conduct of magic in society for the purpose of the process of enforcement and prosecution of magic practitioners. Apart from that, it is also an explanation and exposure to the Muslim community about the dangers of believing in the practice of magic and its use that can lead to the deviation of the beliefs of a Muslim. This study is based on the Results of the Muzakarah of the Fatwa Committee of the National Council for Islamic Religious Affairs Malaysia: Law on the belief in the practice of magic and its use according to Islamic perspective has been gazetted as a Fatwa in several State Fatwa Departments in Malaysia. Violation of the fatwa decision that has been gazetted as an offense because it is considered an insult to Islam and the Religious Authority. The objective of this study will be to discuss the characteristics of superstitious practices, forms of magic practices, the characteristics of magic practitioners, in brief, the role of the authorities in combating magic practices. The methodology used in this study is a library study that is the analysis of documents such as books and articles. It is hoped that these guidelines can also provide understanding and explanation to Muslims in this country on the characteristics of the practice of magic, superstition, and magic according to the Islamic perspective with the hope that the Muslim community stays away from all practices that can threaten the faith, threaten the lives of others and affect harmony society if there is no collective effort from all authorities to curb it.